A review of ustekinumab in the treatment of psoriatic arthritis. (14th February 2018) - Roberts, Janet; O'Rielly, Darren D; Rahman, Proton
Psoriatic arthritis is an inflammatory arthritis associated with psoriasis. The IL-23/IL-17 axis is an important pathway in the development of psoriatic disease. Ustekinumab is a fully human monoclonal IgG1 antibody that binds to the p40 subunit of IL-12 and IL-23, which, in turn, inhibits downstream signaling pathways. PSUMMIT-1 and PSUMMIT-2 are two pivotal Phase III trials demonstrating global improvement in primary and secondary outcomes including inhibition of radiographic progression. Therapeutic benefit of ustekinumab for synovitis appears independent of previous disease modifying antirheumatic disease or anti-TNF exposure. At present, the data support the use of ustekinumab in the treatment of psoriatic arthritis after the failure of NSAIDs and conventional disease modifying antirheumatic diseases as an alternative to, or after failure of an anti-TNF agent.